Correlation of Formal Clarity and Rule of Law (Law and Safety, 2021)
Comprehensive analysis of approaches to understanding the essence of the categories of “rule of law” and “formal clarity” has been carried out within the framework of the conducted research. The author in order to properly understand the category of “rule of law”, has provided the views of both international and domestic researchers, who determine its essence.The author of the work has determined the content of the concept of the rule of law on the basis of the characteristics of the rule of law. A comprehensive analysis of the reports of the European Commission and the Venice Commission on the elements of the rule of law has been conducted. Particular attention has been also paid to the essence of the rule of law principles, which are reflected in those documents. The main requirements relating to the rule of law principle, as well as the main purpose of this principle have been provided.The author has conducted the analysis of approaches to understanding and clarifying the essence of formal clarity provided to this category by both domestic and international researchers. The main requirements for formal clarity have been provided. The procedural requirements inherent in formal clarity have been also separately mentioned in the research.On the basis of the conducted complex characteristic and defining the essence of the categories of “rule of law” and “formal clarity” the author has carried out the analysis of their parity. The approaches of domestic and international researchers in this regard have been provided. It has been emphasized that one of the fundamental aspects of the protection of human rights and freedoms is the formal clarity of law.It has been noted in the conclusion that the formal clarity of law implies a set of precise, unambiguous and transparent legal requirements for both lawmaking and law-enforcement processes designed to ensure the realization of human rights, interests and freedoms, as well as protection against possible manifestations of state arbitrariness that makes it possible to avoid a number of mistakes, offenses and misunderstandings of life situations.
Keywords: law; law principles; rule of law; rule of law principle; formal clarity; clarity; clarity of law